1992
DOI: 10.1128/jb.174.4.1378-1387.1992
|View full text |Cite
|
Sign up to set email alerts
|

Iron transport systems of Serratia marcescens

Abstract: Serratia marcescens W225 expresses an unconventional iron(III) transport system. Uptake of Fe3+ occurs in the absence of an iron(III)-solubilizing siderophore, of an outer membrane receptor protein, and of the TonB and ExbBD proteins involved in outer membrane transport. The three SfuABC proteins found to catalyze iron(III) transport exhibit the typical features of periplasmic binding-protein-dependent systems for transport across the cytoplasmic membrane. In support of these conclusions, the periplasmic SfuA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 57 publications
2
64
1
1
Order By: Relevance
“…Two operons encoding homologues of Fe 3+ transporters in other bacteria have been annotated in P. aeruginosa, PA5216-5217 (homologue of the HitABC system in Haemophilus influenzae) (Sanders et al, 1994) and PA4687-4688 (homologue of the SfuABC and FbpABC systems in Serratia marcescens and Neisseria spp., respectively) (Adhikari et al, 1996;Angerer et al, 1992). Disruption of PA5216 (45 % identical to HitA) and PA4687 (30 % identical to SfuB) in K2931, yielding the triple knockout strain K2556, did not further compromise citrate-promoted growth in EDDA-containing medium (Fig.…”
Section: Contribution Of the Pcoa Ferroxidase To Citratepromoted Fe Amentioning
confidence: 92%
“…Two operons encoding homologues of Fe 3+ transporters in other bacteria have been annotated in P. aeruginosa, PA5216-5217 (homologue of the HitABC system in Haemophilus influenzae) (Sanders et al, 1994) and PA4687-4688 (homologue of the SfuABC and FbpABC systems in Serratia marcescens and Neisseria spp., respectively) (Adhikari et al, 1996;Angerer et al, 1992). Disruption of PA5216 (45 % identical to HitA) and PA4687 (30 % identical to SfuB) in K2931, yielding the triple knockout strain K2556, did not further compromise citrate-promoted growth in EDDA-containing medium (Fig.…”
Section: Contribution Of the Pcoa Ferroxidase To Citratepromoted Fe Amentioning
confidence: 92%
“…This coincides with experimental evidence demonstrating that a functional FbpA pathway is independently capable of acquiring cellular iron from ferric-dipyridyl in the periplasm of E. coli (Adhikari et al, 1995) and is the basis on which the closely related sfu operon was cloned and identified (Zimmermann et al, 1989). Genetic and biochemical similarities between the Sfu and Fbp pathways, coupled with the identification of numerous homologues within the Neisseriaceae (N. gonorrhoeae, N. meningitidis), Pasteurellaceae (H. influenzae, Pasteurella haemolytica, Actinobacillus actinomycetemcomitans) and Enterobacteriaceae (Serratia marcescens, Yersinia enterocolitica), suggest that this system represents a common and related mechanism of iron uptake within Gram-negative bacteria (Murray et al, 1991;Angerer et al, 1992;Genco et al, 1994;Sanders et al, 1994;Adhikari et al, 1995;Saken and Heesemann, GenBank submissions). As further periplasmic iron-binding proteins are identified, it would be advantageous to apply a standard non-species-specific nomenclature to describe these homologues, of which the only one in use to date is the term applied by recommendation of the Sixth International Pathogenic Neisseria Conference, ferric binding protein (FbpA; Berish et al, 1990;Confer, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These two highly conserved tyrosines may then be used to construct a short sequence motif, (N/Y)XYY, to identify new FbpA family members. Although Asn 200 is not absolutely conserved, because three of 41 FbpAs contain a Tyr substitution, this Tyr is present in the FbpA from Serratia marcescens, which is known to be involved in iron transport (41).…”
Section: Discussionmentioning
confidence: 99%